Effective nutritional ergogenic aids - Applegate, E. (International Journal of Sport Nutrition and Exercise Metabolism, 1999)
Athletes use a variety of nutritional ergogenic aids to enhance performance. Most nutritional aids can be categorized as a potential energy source: carbohydrates, protein and amino acid, dietary antioxidants, such as vitamins C and E and carotenes, creatine, caffeine. The effects of this ergogenic aids are discussed.